(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The city is a unique dynamic phenomenon , which embodies the features of the post-industrial society and traditional cultural whole. The city is a combination of two spaces: the geographical, physical and semantic, symbolic (cultural).The geography of the city – a semantic space that has its own history, symbols, rational order. The symbolic significance of the city lies in the understanding of history, values, purity siting, etc. Over time, the impact of changes in the population of the city, capturing architectural forms and everyday socio-cultural practices. Saving urban cultural space in its original form, it is impossible, but it is necessary to study and knowledge of the city as part of a particular historical period, the importance of preserving the urban cultural space in today’s realities. Key words: The phenomenon of the city, urban cultural space, transparency of borders, culture, images, subculture, symbols, signs.